Relativistic density functional theory with finite-light-speed correction for the Coulomb interaction: a non-relativistic-reduction-based approach. (7th October 2020) - Naito, Tomoya; Akashi, Ryosuke; Liang, Haozhao; Tsuneyuki, Shinji
Abstract: The Breit correction, the finite-light-speed correction for the Coulomb interaction of the electron–electron interaction in O 1 / c 2, is introduced to density functional theory (DFT) based on the non-relativistic reduction with the local density approximation. Using this newly developed relativistic DFT, it is found that the possible outer-most electron of lawrencium atom is the p orbital instead of the d orbital, which is consistent with the previous calculations based on wave-function theory. A possible explanation of the anomalous behavior of its first ionization energy is also given. This DFT scheme provides a practical calculation method for the study of properties of super-heavy elements.